PENGEMBANGAN PRODI D-3 SENI KULINER SEBAGAI SENTRA INOVASI DAN KEWIRAUSAHAAN UMKM PANGAN BERBASIS MAKANAN TRADISIONAL INDONESIA - Dimas Bayu Pinandoyo; Swastono Putro Pirastyo; Anindita Budi Astuti, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Indonesia is lacking of center of inovation and enterpreneur for traditional culinary based Small and Medium Enterprise (SME). This paper writen as reference to develop vocational higher aducation as traditional culinary based innovation and entrepreneur center for SME. The development was conducted by mapping the problem together with SME, conducted scientific approach as alternative of problem solver, bridging SME’s needs by involving in research and community service grants, and provided scientific references for SME. By this scheme, Art Culinary Diploma progame of Politeknik Negeri Media Kreatif had produced 4 articles in term of application of food quality standard in SME, 3 packaging designs for traditional culinary based SME, 2 food formulations for traditional culinary based SME, and 6 formulation on the way for western java traditional culinary “nasi liwet” from Bogor. Vocational Higher eductaion proved to play vital role in supporting empowerment, sustainability, and independence of SME.